Physiotherapy and Rehabilitation Management of Musculoskeletal Affections in Canines - Ratnu, Devangini A.; Parikh, Pinesh V. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present work done on physiotherapy and rehabilitation techniques of locomotor system in canine practice is very meagre, especially on physical assessment and diagnostic findings of chronic complains of locomotor affections especially musculoskeletal in dogs with failed medical treatment and no surgical intervention was possible. Nine dogs (5 in the age group of >5 years, three of age group of 1 to 5 years, and one in the age group of
Keywords: Canine,; Musculoskeletal affections; Physiotherapy; Rehabilitation Techniques